Copolymerization as a Strategy to Combine Epoxidized Linseed Oil and Furfuryl Alcohol: The Design of a Fully Bio-Based Thermoset - Pin, Jean-Mathieu; Guigo, Nathanaël; Vincent, Luc; Sbirrazzuoli, Nicolas; Mija, Alice (ChemSusChem, 2015)
Epoxidized linseed oil and furfuryl alcohol are bio‐sourced monomers known for their high‐potential applications in materials science. In this work, we propose the association of these monomers through copolymerization reactions with the target to design fully bio‐based thermosets. Herein, investigations on cationic polymerization reactivity have been explored using differential scanning calorimetry. The obtained structures have been confirmed by IR spectroscopy and 2 D NMR spectroscopy, which revealed the principal chain connections. In spite of the multiple capabilities of chemical connections, which include copolymerization and cross‐linking, the obtained networks are homogeneous as confirmed by dynamic mechanical analysis and SEM. Furthermore, the copolymer demonstrates a semiductile behavior if subjected to tensile measurements (tensile strain at break ≈40 %), which is a significant advance in terms of its applications as a furanic bio‐based thermoset material. Oil on troubled waters: An original combination of epoxidized linseed oil and furfuryl alcohol as bio‐based monomers is proposed to design fully bio‐based materials with tailored mechanical properties.